Analysis of the Discovery Learning Model in Social Studies Instruction for Eighth-Grade Students at SMPN 30 Padang - Lovely Andika Santoso; Sri Rahayu; Yanti Sri Wahyuni (Jurnal Kiprah Pendidikan, 2025)
This study aims to examine the implementation of the Discovery Learning model in Social Studies (IPS) learning for eighth-grade students at SMP Negeri 30 Padang. The background of this research stems from the need to apply innovative learning strategies that can enhance students’ active participation and understanding during the learning process. This research employed a qualitative approach with a descriptive method. The subjects consisted of Social Studies teachers and eighth-grade students, selected through purposive sampling. Data were collected through observation, interviews, and documentation. The findings indicate that the implementation of Discovery Learning was carried out through six stages: stimulation, problem formulation, information gathering, data processing, verification, and drawing conclusions. The application of this model encouraged students to think critically, actively ask questions, and discover the concepts of the learning material independently. The teacher’s role was primarily as a facilitator guiding students through the discovery process. Overall, the use of the Discovery Learning model had a positive impact on the quality of Social Studies learning, particularly in fostering students’ independence and active learning.